Action Research: Bridging the Gap Between Theory and Practice - Vinit A. Sinha; Amit J. Pimprikar (AG Volumes, 2024)
Action Research is a method that is iterative and participatory, with the objective of resolving real-world issues through active collaboration and reflection. Its principles prioritize practical outcomes, reflexivity, and collaboration. Action Research is a method in which practitioners collaborate with researchers to implement and evaluate interventions in the fields of education, healthcare, as well as organizational change. Action Research facilitates the integration of theoretical insights via practical applications, thereby ensuring that solutions are both directly beneficial to practice and informed by research, thereby bridging the divide between theory and practice. This review paper investigates these dimensions, demonstrating the effective integration of scholarly inquiry and real-world problem-solving that Action Research facilitates.